Knowledge and engagement of the sustainable development goals among undergraduate business students - Aldazabal , Edurne; Altuzarra, Amaia (Journal of Management and Business Education, 2023)
This paper analyses the level of knowledge and engagement of the students of the Bachelor's Degree in Business Administration and Management (GADE) of the Faculty of Economics and Business (Gipuzkoa Section) of the University of the Basque Country (UPV/EHU) on the SDGs using Multiple Correspondence Analysis and Cluster Analysis. This analysis makes it possible to identify different patterns or profiles of student behavior in relation to sustainability. The results show the coexistence of four different patterns of behavior in relation to knowledge, perception, and commitment to the Sustainable Development Goals (SDGs) and sustainability among students. We identify a first group comprising 23.4% of students with low knowledge and high commitment to the SDGs; a second group that includes 30.4% of students with high knowledge of and commitment to the SDGs; a third group comprising 30% of students with low knowledge of and commitment to the SDGs; and finally, a fourth group comprising 16.2% of students with high knowledge of and low commitment to the SDGs. This scenario suggests the necessity to make further progress in the incorporation of the sustainable development dimension in the teaching-learning processes.